God and Blackness : Race, Gender, and Identity in a Middle Class Afrocentric Church - Abrams, Andrea C. (Book collections on Project MUSE., 2014)
Offers an ethnographic study of blackness as it is understood within a specific community--the First Afrikan Presbyterian Church, a middle class Afrocentric congregation located in a suburb of Atlanta, Georgia. Drawing on nearly two years of participant observation and in-depth interviews, the author examines how this community has employed Afrocentrism and black theology as a means of negotiation the unreconciled natures of thoughts and ideals that are part of being both black and American.